Comparing gastrulation in flies: links between cell biology and the evolution of embryonic morphogenesis - Lemke, Steffen; Kale, Girish; Urbansky, Silvia (Mechanisms of development, 2020)
For decades, Drosophila gastrulation has been at the forefront of investigations into the molecular and cell biological principles by which tissues are formed and shaped into organs. Recent work has started to uncover how evolution shaped the elements and the processes of gastrulation during the early divergence of Drosophila and other flies. Here we look at the macroscopic processes that define fly gastrulation and how molecular patterning provides spatial instructions relevant for epithelial remodeling. We integrate studies of gastrulation in other flies to outline how epithelial morphogenesis changed over the course of fly evolution. This work exposes links between morphogenetic differences and changes in molecular patterning and signal transduction. We conclude with a discussion of how gastrulation can evolve through changes in the expression and regulation of patterning genes, or through changes in how such information is relayed to the cytoskeleton.